2020
DOI: 10.1177/0363546520941859
|View full text |Cite
|
Sign up to set email alerts
|

The Hip Suction Seal, Part II: The Effect of Rim Trimming, Chondrolabral Junction Separation, and Labral Repair/Refixation on Hip Distractive Stability

Abstract: Background: The acetabular labrum contains free nerve endings, and an unstable labrum can result in increased femoral head movement during hip motion. This can be caused by chondrolabral junction (CLJ) separation, especially in association with pincer-type femoroacetabular impingement, and may contribute to hip pain. Hypothesis: Rim resection alone has no effect on suction seal biomechanics. Further, separation of the CLJ changes hip suction seal biomechanics when compared with those of the native state, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…12,14,16,19 Despite the progress of instruments and arthroscopic techniques, the treatment of irreparable labral tears remains a great challenge for surgeons. With the importance of the chondrolabral junction being studied and discussed in several basic science studies, 22,23 labral augmentation is preferable in some cases compared with labral reconstruction for the preservation of native innervation and vascularization. Although excellent short- to midterm clinical outcomes of labral augmentation with autograft were reported by recent studies, 6,24 the potential advantages of labral augmentation compared with labral reconstruction remain unverified.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,16,19 Despite the progress of instruments and arthroscopic techniques, the treatment of irreparable labral tears remains a great challenge for surgeons. With the importance of the chondrolabral junction being studied and discussed in several basic science studies, 22,23 labral augmentation is preferable in some cases compared with labral reconstruction for the preservation of native innervation and vascularization. Although excellent short- to midterm clinical outcomes of labral augmentation with autograft were reported by recent studies, 6,24 the potential advantages of labral augmentation compared with labral reconstruction remain unverified.…”
Section: Discussionmentioning
confidence: 99%
“…23 The function and importance of the acetabular labrum and the labral suction seal mechanism in hip biomechanics have been demonstrated. 24 Restoration of labral anatomy and function are key factors to obtain favorable outcomes following FAIS arthroscopic management. Labral repair is currently the preferred surgical option when facing labral tears, with clinical mid-term to long-term data supporting its use.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last decade, a number of cadaveric studies have demonstrated the importance of the acetabular labrum in preserving normal hip function [37][38][39][40][41]. Composed of a complex fibrocartilaginous matrix, the hip labrum in combination with the transverse acetabular ligament form an uninterrupted ring around the acetabulum [40].…”
Section: Labral Functionmentioning
confidence: 99%